Transcription frequency modulates the efficiency of an attenuator preceding the rpoBC RNA polymerase genes of Escherichia coli: possible autogenous control. - Steward, K L (1992)
Expression of the rpoBC genes encoding the beta and beta' RNA polymerase subunits of Escherichia coli is autogenously regulated. Although previous studies have demonstrated a post-transcriptional feedback mechanism, complex transcriptional controls of rpoBC expression may also contribute. We show that an attenuator (rpoBa) separating the ribosomal protein (rpl) genes from the rpoBC genes in the rplKAJLrpoBC gene cluster is modulated in its efficiency in response to changes in the frequency of transcription initiated by promoters located upstream. A series of rplJLrpoBalacZ transcriptional fusions was constructed on lambda vectors in which transcription into the rpoBa attenuator was varied by using a variety of promoters with different strengths. beta-galactosidase assays performed on monolysogens of the recombinant phage show that with transcription increasing over a 40-fold range, readthrough of rpoBa decreases from 61% to 19%. In contrast, two other well-characterized terminators show nearly constant efficiencies over a similar range of transcription frequencies. Using a set of phage P22 ant promoter variants with single-nucleotide changes in the promoter consensus sequences also demonstrates that the modulation of rpoBa function appears to be unrelated to the phenomenon of 'factor-independent antitermination' reported by others. The implications for autogenous control of RNA polymerase synthesis are discussed.